ADAPTIVE IMMUNITY IN INFANTS AND CHILDREN WITH ALLERGIES - Kusumawardani, Netta; Permatasari, Zendy Indah; Tasbieta, Alfi Asyadda; Santi, Dwi Rukma (JURNAL WIDYA MEDIKA, 2026)
The immune system consists of innate immunity and adaptive immunity, which interact to protect the body from pathogens and foreign substances. In children, the adaptive immune system is not fully developed, so the function of B cells and T cells, as well as immune tolerance mechanisms, is still limited. This condition can increase susceptibility to allergies, especially when influenced by environmental factors, genetics, and gut microbiota. Various studies have shown that disturbances in the adaptive immune balance, such as the dominance of Th2 responses, low regulatory B cell function, and changes in pro-inflammatory cytokines, play a significant role in triggering allergic reactions. Furthermore, environmental exposures such as air pollution, cigarette smoke, house dust allergens, and skin barrier disruption contribute to worsening sensitization and increasing the risk of atopic dermatitis, food allergies, and allergic rhinitis in children. This literature review analyzes articles that discuss the mechanisms of allergies in children through an adaptive immune system approach. The results indicate that allergies are a multifactorial condition influenced by immunological imbalance, activation of specific molecular pathways, and an unstable microbiota. The adaptive immune system in allergic children tends to exhibit hyperresponsiveness, including increased TfH cell activity, decreased regulatory T cells, increased neutrophils, and high production of allergenic cytokines. These findings emphasize that understanding adaptive immune development early in life is crucial for more effective allergy prevention and treatment strategies in children.